Existence and upper semicontinuity of random attractors for stochastic p-Laplacian equations on unbounded domains - Jia Li; Yangrong Li; Hongyong Cui (Electronic Journal of Differential Equations, 2014)
The existence of a pullback attractor is established for a stochastic p-Laplacian equation on $\mathbb{R}^n$. Furthermore, the limiting behavior of random attractors of the random dynamical systems as stochastic perturbations approach zero is studied and the upper semicontinuity is proved.